Subungual glomus tumor - Salem, Yousif; Al Khalifa, Jawaher; El Shayeb, Ashraf (International Surgery Journal, 2019)
We are presenting a twenty-year-old female, who presented with distal left little finger pain for more than a year. Pain is very localized to the nail root, and increases in severity in cold weather or exposed to cold water. The patient was diagnosed based on history and physical examination to have a glomus tumor and surgical excision was done after that and histopathological examination confirmed the clinical diagnosis. The aim of this case is to present a rare disease and to show the pronounced treatment of such a case.